2022
DOI: 10.1002/fsn3.2984
|View full text |Cite
|
Sign up to set email alerts
|

Total saponins from quinoa bran alleviate high‐fat diet‐induced obesity and systemic inflammation via regulation of gut microbiota in rats

Abstract: Obesity is a serious and increasing health problem, which is considered to be strongly associated with chronic metabolic diseases, including type 2 diabetes mellitus (T2DM), hyperlipidemia, hypertension, and nonalcoholic steatohepatitis (Han & Lean, 2016).The fundamental feature of obesity is the extreme disequilibrium between energy uptake and expenditure, leading to abnormal excessive growth of adipose tissue (Lin & Lin-Shiau, 2006). Growing evidence suggests that the typical characteristic of obesity is low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Saponins were reported to improve insulin resistance and suppress visceral fat accumulation; for example, in the staple food of Chenopodium quinoa Willd. (Li et al., 2022 ); moreover, sea cucumber extracts revealed favorable effect in obese high‐fat fed rats through its effect on pancreatic lipase, reducing total cholesterol, LDL, and total triglycerides (Guo et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Saponins were reported to improve insulin resistance and suppress visceral fat accumulation; for example, in the staple food of Chenopodium quinoa Willd. (Li et al., 2022 ); moreover, sea cucumber extracts revealed favorable effect in obese high‐fat fed rats through its effect on pancreatic lipase, reducing total cholesterol, LDL, and total triglycerides (Guo et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The saponins in quinoa are characterized by their low bioavailability, poor absorption, and prolonged intestinal residence. These characteristics indicate the potential availability for metabolism by intestinal microorganisms and that they can serve as a source of secondary glycosides or aglycosides ( 42 ). Studies have shown that ( 43 ) Under the action of intestinal flora, quinoa saponin can be effectively hydrolyzed into sapogenin by the host, the release of sapogenin is related to the initial microbial composition of intestinal microflora, and the initial intestinal microflora interferes with the later conversion process of sapogenin of quinoa saponin through some mechanism.…”
Section: The Regulatory Effects Of Quinoa Bioactive Components On Int...mentioning
confidence: 99%
“…Within the intestines, quinoa saponins can be effectively microbially hydrolyzed to yield sapogenin, the release of which has been shown to influence the initial microbial composition of intestinal microflora, which in turn interferes with the subsequent conversion of sapogenin. In this regard, Li et al ( 42 ) have reported that total quinoa saponins have a bidirectional regulatory effect on intestinal microorganisms, with the ability to selectively promote the growth of beneficial bacteria. For example, treatment with quinoa saponins has been found to promote a significant increase in the relative abundance of Lactobacillus , has a beneficial effect on butyrate-producing bacteria, promotes health by enhancing the relative abundance of anti-inflammatory intestinal microbiota, inhibits the excessive growth of harmful bacteria, and reduces the production of lipopolysaccharides (LPS).…”
Section: The Regulatory Effects Of Quinoa Bioactive Components On Int...mentioning
confidence: 99%
“…To assess the effects of PSM under anaerobic conditions that are likely present in the soil, the experiments need to be conducted under such conditions. Previous research has explored alterations in bacterial communities by PSMs under anaerobic conditions in gut microbiota (Ghimire et al 2022;Huang et al 2022;Li et al 2022;Xu et al 2020), which can help predict the effects of PSMs in anaerobic soil conditions. It is also crucial to accurately replicate the rhizosphere environment, which has a gradient of physical, chemical, and biological factors (Kuzyakov and Razavi 2019).…”
Section: An In Vitro Pseudo-rhizosphere System To Analyze Soil Microb...mentioning
confidence: 99%